2020
DOI: 10.3390/diagnostics10080534
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imaging Biomarkers in the Assessment of Sarcopenia

Abstract: Background: The diagnosis of sarcopenia through clinical assessment has some limitations. The literature advises studies that include objective markers along with clinical assessment in order to improve the sensitivity and specificity of current diagnostic criteria. The decrease of muscle quality precedes the loss of quantity, so we studied the role magnetic resonance imaging biomarkers as indicators of the quantity and quality of muscle in sarcopenia patients. Methods: a cross-sectional analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
0
15
0
2
Order By: Relevance
“…This may result from fibrosis in the muscle ( Figure 2 ). It was hypothesized by Sanz-Requena et al [ 21 ] that the fat content in lower leg muscles would cause a decrease of apparent diffusion coefficient. Therefore, decrease of diffusivities in the patient’s TA muscle may also indicate its dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…This may result from fibrosis in the muscle ( Figure 2 ). It was hypothesized by Sanz-Requena et al [ 21 ] that the fat content in lower leg muscles would cause a decrease of apparent diffusion coefficient. Therefore, decrease of diffusivities in the patient’s TA muscle may also indicate its dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that the difference in body fat between Japanese and Brazilian older individuals may have a greater effect on functional capacity than LBM. A recent study suggested that imaging-derived muscle quality based on magnetic resonance imaging indicators can help to identify older individuals at risk of developing sarcopenia at an early stage [ 24 ], and also provides helpful information for understanding the potential role of muscle quality in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50] Furthermore, as most patients receive orthodontic treatment during childhood, further development of radiation-free techniques, such as MRI are highly desirable. [51][52][53] F I G U R E 1 Schematic depiction of bone and tooth multiscale hierarchical structure from macroscopic bone (up raw) and tooth (bottom raw) to their nanoscopic elements. This hierarchical organization is the genesis of bone and dentine properties, including stress tolerance, adaptability and development during the growth process.…”
Section: The Orofacial System As a Hierarchical Multiscale Complex Systemmentioning
confidence: 99%
“…In recent years, in addition to the conventional x‐ray computer tomography (CT) and the cone‐beam computer tomography (CBCT), MRI has shown great potential in dentistry 46‐50 . Furthermore, as most patients receive orthodontic treatment during childhood, further development of radiation‐free techniques, such as MRI are highly desirable 51‐53 …”
Section: Introductionmentioning
confidence: 99%